THEORETICAL AND LEGAL ANALYSIS OF THE CONCEPT OF CYBER-SPELLING CRIME, HISTORY OF ORIGIN AND CONTENT (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the theoretical and legal essence, historical development, and contemporary criminal-law significance of cyber extortion. The study examines the issue on the basis of the Criminal Code and Criminal Procedure Code of the Republic of Uzbekistan, national legislation on cybersecurity, relevant decisions of the Plenum of the Supreme Court, as well as the experience of the United States, the United Kingdom, Germany, and the approaches reflected in the Budapest Convention on Cybercrime. The article substantiates that cyber extortion should not be viewed merely as an online form of traditional extortion, but rather as a complex criminal-law phenomenon that simultaneously infringes upon property, information resources, personal data, digital reputation, and economic security.